1993
DOI: 10.1366/0003702934067333
|View full text |Cite
|
Sign up to set email alerts
|

Rheo-Optical Fourier Transform Infrared and Raman Spectroscopy of Polymers

Abstract: This article is intended to review recent results of simultaneous mechanical and Fourier transform infrared spectroscopic—so-called rheo-optical—measurements for polymer deformation studies. The technique will also be discussed in terms of the application of Fourier transform near-infrared light-fiber and Raman spectroscopy. Specifically, data on the bidirectional drawing of poly(ethylene terephthalate) and the strain-induced conformational changes of poly(vinylidene fluoride) will be presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…These behaviors of 〈P 2 〉 are consistent with those estimated with the IR and the NIR spectroscopies [11][12][13][14][15]. It has been demonstrated that the orientation of the amorphous chains proceeds rapidly in the yielding region, as well as the crystalline chains, though the values of the orientation function of the amorphous chains are appreciably smaller than those of the crystalline chain [11][12][13]16,43]. These orientational behaviors of the amorphous chains seem to be consistent with the present results for the crystalline chains.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…These behaviors of 〈P 2 〉 are consistent with those estimated with the IR and the NIR spectroscopies [11][12][13][14][15]. It has been demonstrated that the orientation of the amorphous chains proceeds rapidly in the yielding region, as well as the crystalline chains, though the values of the orientation function of the amorphous chains are appreciably smaller than those of the crystalline chain [11][12][13]16,43]. These orientational behaviors of the amorphous chains seem to be consistent with the present results for the crystalline chains.…”
Section: Resultssupporting
confidence: 91%
“…During such dual plastic deformations, large-scale transformation of the semi-crystalline morphology takes place, and collapse of the spherulite structures, necking of the sample specimens, and rearrangement of the lamellar crystals and the polymer chains have been observed [1][2][3][4][5][6]. Although various models, such as the lamellar local-melting and recrystallization model [4,7], and the lamellar cluster model [3,[8][9][10], have been proposed for the deformation mechanism, such complicated changes in the hierarchical structures of semicrystalline polymers are still controversial.Spectroscopic techniques have been applied for the orientational behavior of PE during elongation [11][12][13][14][15][16][17]. The infrared (IR) spectroscopy has been applied intensively, and it has been established that the molecular chains in the crystalline and amorphous phases orientate toward the draw direction [11][12][13][14].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Barton and Noda et al [5][6][7][8] also assigned NIR bands by correlation with IR bands using two-dimensional correlation spectroscopy. Ozaki et al and Siesler et al [9][10][11][12][13][14][15][16] recently demonstrated that NIR spectroscopy can be useful for the structural characterization of polymeric materials, foods and bio-based materials.…”
Section: Introductionmentioning
confidence: 99%